Polyelectrolyte multilayer modified nanofiltration membranes for the recovery of ionic liquid from dilute aqueous solutions. Issue 39 (16th June 2017) - Avram, Alexandru M.; Ahmadiannamini, Pejman; Vu, Anh; Qian, Xianghong; Sengupta, Arijit; Wickramasinghe, S. Ranil
ABSTRACT: The feasibility of nanofiltration membranes fabricated by static polyelectrolyte layer‐by‐layer deposition of poly(styrene sulfonate) and poly(allylamine hydrochloride) on poly(ether sulfone) ultrafiltration and alumina microfiltration membranes for the recovery of ionic liquid from low molecular weight sugar was investigated. The surface properties of these modified membranes were correlated with their performances. The selectivity for 1‐butyl‐3‐methylimidazolium chloride over cellobiose and glucose was found to be as high as 50.5/2.3 for modified alumina and 32.3/3.5 for modified poly(ether sulfone) membranes with optimized number of bilayers. The values for membrane permeance were 4.8 and 2.5 L m −1  h 2  bar −1, respectively. For low depositions, the separation mechanism was predominantly governed by size‐exclusion. For higher depositions, the enhanced negative zeta potential of the modified membranes suggested preferred dominating electrostatic interactions, resulting in high selectivity of ionic liquids over low molecular weight sugars. At very high depositions, the molecular weight cut‐off of the membrane becomes constricting for size‐exclusion effect. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45349. Abstract :